2018
DOI: 10.1093/abm/kax052
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Nutrition Literacy and Quality of Self-monitoring in Behavioral Weight Loss

Abstract: Background Few have examined nutrition literacy (i.e., capacity to process and make informed nutritional decisions) in behavioral weight loss. Nutrition literacy (NL) may impact necessary skills for weight loss, contributing to outcome disparities. Purpose The study set out to: identify correlates of NL; evaluate whether NL predicted weight loss, food record completion and quality, and session attendance; and investigate whether the relations of race and education to weight loss were mediated by NL and self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
14
0
3
Order By: Relevance
“…Among them, liraglutide has proven to be one of the most commonly prescribed pharmacotherapy for treating obesity, due in large part to the pronounced weight loss and relatively modest profile of adverse events 21,22,53 . While all of these approved therapies, including liraglutide, are successful at producing initial weight loss, each is limited in the magnitude, and for some, the duration of efficacy 21,40,54,55 . Indeed, a well-documented phenomenon undoubtedly contributing to the resistance of these drugs in producing a greater duration and magnitude of weight loss is the host of counter-regulatory metabolic and neuroendocrine changes that occur with weight loss 54 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among them, liraglutide has proven to be one of the most commonly prescribed pharmacotherapy for treating obesity, due in large part to the pronounced weight loss and relatively modest profile of adverse events 21,22,53 . While all of these approved therapies, including liraglutide, are successful at producing initial weight loss, each is limited in the magnitude, and for some, the duration of efficacy 21,40,54,55 . Indeed, a well-documented phenomenon undoubtedly contributing to the resistance of these drugs in producing a greater duration and magnitude of weight loss is the host of counter-regulatory metabolic and neuroendocrine changes that occur with weight loss 54 .…”
Section: Discussionmentioning
confidence: 99%
“…While all of these approved therapies, including liraglutide, are successful at producing initial weight loss, each is limited in the magnitude, and for some, the duration of efficacy 21,40,54,55 . Indeed, a well-documented phenomenon undoubtedly contributing to the resistance of these drugs in producing a greater duration and magnitude of weight loss is the host of counter-regulatory metabolic and neuroendocrine changes that occur with weight loss 54 . Regardless of the precise mechanisms contributing to this phenomenon, a growing appreciation is that the central nervous system (CNS) is sensing multiple changes in redundant hormonal systems that drive hyperphagia to restore a previous body weight set point 54 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustained monitoring involves an increased knowledge about diet and activity levels for effective decision-making related to weight control. Findings from previous studies have suggested that sustained self-monitoring is a vital element of treating overweight adults (Rosenbaum, Clark, Convertino, Call, Forman, & Butryn, 2018;Perenc et al, 2015;Asch, Muller, & Volpp, 2012).…”
Section: Introductionmentioning
confidence: 99%